2008
DOI: 10.1590/s0004-28032008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de alterações na cavidade oral em pacientes com doença do refluxo gastroesofágico

Abstract: 2RESUMO -Racional -A doença do refluxo gastroesofágico, afecção de elevada e crescente incidência, pode se manifestar através de sintomas típicos (pirose e regurgitação) e atípicos (pulmonares, otorrinolaringológicos e bucais). Objetivo -Analisar as alterações na cavidade oral de pacientes com a doença do refluxo gastroesofágico. Métodos -Foram estudados 100 pacientes, sendo 50 acometidos por doença do refluxo gastroesofágico (grupo 1) e 50 controles (grupo 2). Todos os pacientes foram submetidos a exame clíni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
7
1
8
Order By: Relevance
“…Because CP patients' motor and cognitive impairments often result in difficulty swallowing, 29 this behavior, combined with GER, may contribute to an increase in the prevalence of dental erosion; the acidic material from the stomach would take longer to be swallowed or spat out, remaining in contact with dental tissues for extended periods of time. As in previous papers, 27 the present study found no association be- tween reflux and dental caries, indicating that the methodology employed was likely inadequate for the investigation of this issue.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…Because CP patients' motor and cognitive impairments often result in difficulty swallowing, 29 this behavior, combined with GER, may contribute to an increase in the prevalence of dental erosion; the acidic material from the stomach would take longer to be swallowed or spat out, remaining in contact with dental tissues for extended periods of time. As in previous papers, 27 the present study found no association be- tween reflux and dental caries, indicating that the methodology employed was likely inadequate for the investigation of this issue.…”
contrasting
confidence: 49%
“…Few studies have linked dental caries to GER, and there is no consensus on whether patients with this condition have a greater or lesser caries experience when compared to healthy individuals. 25,27 Some studies demonstrate that GER is associated with the development of dental caries, 28 whereas other studies report that this disorder plays a protective role against dental caries.…”
mentioning
confidence: 99%
“…In our sample, there was a predominance of females, which was in agreement with others studies, where 69.5% and 64%, respectively, were females 17,18 .…”
Section: Discussionsupporting
confidence: 93%
“…Patients who have gastroesophageal reflux tend to have higher incidence of dental erosions, ulcers, burning mouth, tooth sensitivity and sour taste and a lower incidence of carious lesions 11,62 . This susceptibility to dental erosion highlights the importance of the presence of a dental surgeon in the multidisciplinary team that treat these patients.…”
Section: Methodsmentioning
confidence: 99%